MIGS: therapeutic success of combined Xen Gel Stent implantation with cataract surgery - Hohberger, Bettina; Welge-Luessen, Ulrich-Christoph; Lämmer, Robert (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: Glaucoma, a common disease in the elderly population, is frequently coexistent with cataract. While the combination of filtration surgery and cataract surgery is a challenging topic with limited success, minimal invasive glaucoma surgery (MIGS), such as Xen Gel Stents, seems to provide promising results. The aim of this study was to investigate the complete and qualified therapeutic success of Xen Gel Stent implantation with (XenPhaco) and without cataract surgery. METHODS: One hundred and eleven open-angle glaucoma eyes underwent implantation of Xen45 Gel Stent (AqueSys, Inc.) with or without cataract operation. Complete therapeutic success was defined as target intraocular pressure (IOP) < 18 mmHg at any time point within 6 months of follow-up without local antiglaucomatous therapy or further surgical interventions. Qualified success was defined as target IOP <18 mmHg with additional 1-2 local antiglaucomatous eye drops. Failure included all cases with the necessity of at least three local antiglaucomatous eye drops or additional glaucoma surgery. RESULTS: Combined implantation of Xen Gel Stent with cataract surgery was performed in 30 eyes and stand-alone Xen Gel Stent implantation was performed in 81 eyes. A complete therapeutic success was achieved in 46.9% of single Xen Gel Stent implantation, whereas 53.3% was reached with combined XenPhaco. Qualified success was seen in 2.5% in the eyes of the single Xen Gel Stent implantation group and in 3.3% of the combined surgery group. Therapeutic failure rate was 49.4% in the stand-alone group vs 46.7% in the combined group. Data were not significantly different for group and subgroup analyses. CONCLUSIONS: Complete and qualified therapeutic success is similar for the combination of Xen Gel Stent implantation with and without cataract surgery in open-angle glaucoma patients. MIGS using Xen Gel Stent can be recommended in situations if glaucoma surgery is indicated besides coexisting cataract.
EVALuna2:34754